Islamic Viewpoint on Surrogacy with the Second Wife - MUHAMMAD QASIM BUTT; SULTAN SHAH (Hamdard Islamicus, 2021)
Surrogacy is a technique of assisted reproduction that involves the employment of IVF in a distinct way.It is indicated in women who have a problematic uterus due to which they cannot gestate an embryo. Although surrogacy appears to be simple, but ethical, legal, and psychological issues involved in it are complex.A majority of Muslim jurists is against any kind of surrogacy; only a few of them approve it with strict regulatory measures. However, there is some hope for infertile Muslim couples if the surrogate arrangement is made between a man and his second wife. This paper aims to highlight the Islamic viewpoint on the possibility of surrogacy with the second wife.